Severity of Depression and Anxiety Symptoms is Associated with Increased Arterial Stiffness in Depressive Disorder Patients Undergoing Psychiatric Treatment - (:unkn) unknown (My University, 2016)
0

Objective: Depression and anxiety are associated with both subclinical and clinical cardiovascular disease. Endothelial dysfunction, atherosclerosis, and inflammation are some of the underlying mechanisms. Pulse wave velocity (PWV) and augmentation index (AIx) are noninvasive markers for evaluation of arterial stiffness. The aim of this study was to examine the association between arterial stiffness parameters and depression/ anxiety scores in depressive patients undergoing psychiatric treatment.Methods: The study population consisted of 30 patients with depression undergoing psychiatric treatment at least 4 weeks, and 25 age and gender matched healthy controls. Depression and anxiety were assessed by self-reported scales, including the Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI). Measurements of arterial stiffness parameters were performed by using a Mobil-O-Graph arteriograph system, which detects signals from the brachial artery.Results: Baseline characteristics and clinical data were similar between the two groups. BDI and BAI scores were statistically significantly higher in patients with depression (p<0.001, p<0.01). PWV and AIx were statistically significantly higher in patients with depression compared to controls (6.40±1.31 m/s vs 5.51±0.41 m/s and 26.9±12.1 % vs 17.4±11.3 %, p=0.001, p=0.004, respectively). PWV and AIx positively, mildly and statistically significantly correlated with BDI and BAI scores.Conclusion: Arterial stiffness parameters were statistically significantly higher in depressive patients receiving antidepressant treatment. Moreover, arterial stiffness parameters statistically significantly correlated with BDI and BAI. Assessment of arterial stiffness parameters may be useful for early detection of cardiovascular deterioration in depressive patients undergoing antidepressant treatment
Keywords: Farmakoloji ve Eczacılık